The Influence of Influencer Marketing on Purchasing Decisions in Generation-Z (Study on Students who use TikTok at UPN "Veteran" East Java) - Saputra, Mohamad Deka; Ardianto, Alvian Eka; Zanuba S.N, Moh. Ilham; Nugraha, Rusdi Hidayat; Kusumasari, Indah Respati (Jurnal Bisnis dan Komunikasi Digital, 2025)
In the ever-growing digital era, marketing through social media is now one of the most effective strategies to attract consumer attention, generation Z is a generation that is easy to understand today's technological advances, making it possible to attract attention by using social media marketing. This research aims to analyze and thoroughly understand the influence of influencer marketing on purchasing decisions among Generation Z using a qualitative descriptive approach. Through this analysis, it is expected to explore the views and experiences of generation z consumers towards influencer marketing in decision making. So that it can provide meaningful involvement for the development of digital marketing science and can provide a deeper understanding of consumer behavior.